A generalisation of the copair constructions for triangle-saturated graphs - MacDougall J.A. (Utilitas Mathematica, 2004)
All triangle-saturated graphs can be generated from those that are primitive and minimally triangle-saturated. We show how to construct several new infinite families of primitive minimally triangle-saturated graphs, The method is a generalisation of the copair constructions, which have been described previously. For any order n, the number of graphs produced is an exponential function of n.